Assessment of haematological and biochemical alterations in recumbent buffaloes. Issue 11 (2nd November 2022) - Kumari, Ansu; Kumar Jain, Vinod; Kumar Nehra, Anil; Kumar, Manesh; Sharma, Maneesh; Kumar, Aman; Gupta, Sandeep; Singh, Yudhbir
ABSTRACT: The present study was undertaken on adult recumbent buffaloes ( n = 63), which were clustered into six groups based on the history and tentative diagnosis viz., infectious, metabolic, traumatic, abdominal dysfunction, intoxication, and musculoskeletal and nervine. An additional group of 10 adult healthy control buffaloes was also included in the study. The blood, serum, and faecal samples were collected on zero day to perform haematological, blood smear, serum biochemical, and faecal examination, respectively. Also, the similar samples were collected on 5 days post treatment (DPT) in recovered and control animals. Genomic DNA from individual blood samples was isolated and subjected to conventional polymerase chain reaction (PCR) and quantitative PCR for exploring Trypanosoma evansi and Bovine Herpes Virus-1 infections, respectively. The detailed history of recumbent buffaloes revealed the mean age as 5.53 ± 0.34 years and duration of recumbency as 2.61 ± 0.38 days. Younger animals (3.92 ± 0.31 years) having ~14 hours of recumbency period showed recovery and good prognosis. On comparison of serum biochemical parameters of recovered and non-recovered recumbent animals, Aspartate Aminotransferase (AST), creatinine phosphokinase, phosphorus, sodium, and chloride showed significant difference between them ( p < 0.05); thus, indicating their suitability for being prognostic indicators. Out of 63 recumbent animals, 10 (15.87%) showed recovery from recumbency after 5 DPT. The present study recognized the alterations in haemato-biochemical parameters in recumbent buffaloes for the first time.